Disease-related malnutrition in children with cancer: What’s the risk and the impact on patient's outcome? - Bambang Sudarmanto; Citra Primavita (World Nutrition Journal, 2022)
Background: Malnutrition in children with cancer is a common problem, particularly in low-income countries. Risk factors, effects on outcome, and feasible interventions are important to comprehend in managing patients. Objectives: To know the risk and impact of malnutrition in children with patients. Discusion: Children with cancer are at risk of suffering from malnutrition. Malnutrition occurs due to energy imbalance and results from multifactorial interactions, including type of tumors and therapy. Malnutrition can contribute to poor clinical outcome and decreased quality of life. Management of malnutrition in pediatric patients with cancer include screening and nutritional interventions with suitable route of administration based on patient condition.